Two-color coherent control of femtosecond above-threshold photoemission from a Tungsten nanotip - Förster, Michael; Paschen, Timo; Krüger, Michael; Lemell, Christoph; Wachter, Georg; Libisch, Florian; Madlener, Thomas; Burgdoerfer, Joachim; Hommelhoff, Peter (Physical Review Letters, 2016)
We demonstrate coherent control of multiphoton and above-threshold photoemission from a single solid-state nanoemitter driven by a fundamental and a weak second harmonic laser pulse. Depending on the relative phase of the two pulses, electron emission is modulated with a contrast of the oscillating current signal of up to 94%. Electron spectra reveal that all observed photon orders are affected simultaneously and similarly. We confirm that photoemission takes place within 10 fs. Accompanying simulations indicate that the current modulation with its large contrast results from two interfering quantum pathways leading to electron emissio